A taxonomic study of Sedum series Rupestria (Crassulaceae) naturalized in North America - Gallo, Lorenzo; Zika, Peter (Phytotaxa, 2014)
Sedum rupestre L. and its close relatives (Sedum series Rupestria) are native to Europe. Adventive populations in North America were studied both in the field and the herbaria. Our results exclude S. rupestre L. and include recognition of two additional taxa on the continent, which are distinguished with keys and illustrations: Sedum forsterianum documented as a naturalized species in the United States, from Washington, and in British Columbia, Canada and Sedum thartii, naturalized in Colorado, Maine, Ohio, Oregon, Washington and Ontario, Canada. A lectotype is established for S. forsterianum.